(6x-7)²-(5x+7)(5x-7)=36x²-84x+49-(25x²-49)=36x²-84x+49-25x²+49=11x²-84x+98
y(y+6)²-(y+1)(y-6)²=y(y²+12y+36)-(y+1)(y²+12y+36)=
=y³+12y²+36y-(y³+12y²+36y+y²+12y+36)=y³+12y²+36y-y³-12y²-36y-y²-12y-36=
=-y²-12y-36=-(y²+12y+36)=-(y+6)²
100-140a+49a²=(10-7a)²
x⁴+18x²y+81y²=(x²+9y)²
(x²-4x)²-16 =(x²-4x)²-4²=((x²-4x)+4)((x²-4x)-4)=(x²-4x+4)(x²-4x-4)
9b²-25c²-3b+5c=(9b²-25c²)+(-3b+5c)=(3b+5c)(3b-5c)-(3b-5c)=
=(3b-5c)(3b+5c-1)
frac{ x^{2} -y^2}{( x^{2} -xy)^2} = frac{(x+y)(x-y)}{(x(x-y))^2} =frac{(x+y)(x-y)}{x^2(x-y)^2} = frac{x+y}{x^2(x-y)} = frac{x+y}{x^3-x^2y}
(x
2
−xy)
2
x
2
−y
2
=
(x(x−y))
2
(x+y)(x−y)
=
x
2
(x−y)
2
(x+y)(x−y)
=
x
2
(x−y)
x+y
=
x
3
−x
2
y
x+y
(a-3b)²=a²-9b²
a²-3ab+9b²=a²-9b²
a²-6ab+9b²-a²+9b²=0
-6ab+18b²=0
-6b(a-3b)=0
a-3b=0
a=3b
значит при любых значениях удовлетворяющих а=3b, исходное равенство будет верным